ANALYSIS OF BIOGAS UTILIZATION AS ENVIRONMENTALLY FRIENDLY ELECTRICAL ENERGY IN TANA TORAJA - Muh. Rais; Lahming Lahming; Nurlita Pertiwi; Frederik Palallo; Andi Nur Putri (International Conference on Social and Islamic Studies, 2021)
Biogas produced from livestock and agricultural waste is used by the community as a substitute fornatural gas energy and as a substitute for electrical energy to provide gas needs for gas stoves andhousehold electrical energy needs in Tana Toraja Regency. This study aims to analyze the level ofcommunity involvement in Tana Toraja Regency in utilizing biogas as an alternative energy source and asolution for livestock and agricultural waste. Furthermore, by using a quantitative approach, thisresearch also aims to identify the impact of using biogas as an alternative energy for the community froman economic, social and environmental perspective. Biogas is one solution to the scarcity of posil energysources and is an environmentally friendly alternative energy source. This advantage makes Biogas anenergy source that has good prospects as an alternative energy substitute for non-renewable energy inIndonesia, which is currently experiencing an energy crisis, which is characterized by increasingly scarceand high fuel prices which have an impact on the higher production costs of power plants. The existenceof renewable energy is something that is very important to meet energy needs in Indonesia.